Voltage regulation of buck converter with constant power load: An adaptive power shaping control. (October 2021) - He, Wei; Namazi, Mohammad Masoud; Koofigar, Hamid Reza; Amirian, Mohammad Ali; Guerrero, Josep M.
Abstract: In this paper, the problem of voltage regulation of DC–DC buck converter with unknown constant power load (CPL) and input voltage is addressed. A power shaping controller (PSC) based on the passivity theory is proposed to stabilize this system. In addition, borrowing immersion & invariance (I&I) technique, an observer can be designed to estimate CPL and input voltage simultaneously. By combining PSC with I&I observer, an adaptive control scheme is achieved. Besides, the estimate of the domain of attraction is given to rigorously guarantee the convergence property by virtue of the invariant set theory. Then, the locally asymptotic stability of the closed-loop system is established. Finally, the simulation and experimental results show the effectiveness of the proposed control method.